2005
DOI: 10.1103/physrevb.71.045303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an in-plane magnetic field on the photoluminescence spectrum of modulation-doped quantum wells and heterojunctions

Abstract: The photoluminescence (PL) spectrum of modulation-doped GaAs/AlGaAs quantum wells (MDQW) and heterojunctions (HJ) is studied under a magnetic field (B ) applied parallel to the two-dimensional electron gas (2DEG) layer. The effect of B strongly depends on the electron-hole separation (d eh ), and we revealed remarkable B -induced modifications of the PL spectra in both types of heterostructures. A model considering the direct optical transitions between the conduction and valence subband that are shifted in k-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
30
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 27 publications
6
30
0
Order By: Relevance
“…In the inset of Fig. 3, the present theoretical results are compared with fair agreement with recent experimental data [11]. Of course, for high values of the applied magnetic field, a reliable calculation should involve a more realistic type of wave function which would appropriately take into account magnetic-field induced anisotropic effects.…”
supporting
confidence: 58%
See 4 more Smart Citations
“…In the inset of Fig. 3, the present theoretical results are compared with fair agreement with recent experimental data [11]. Of course, for high values of the applied magnetic field, a reliable calculation should involve a more realistic type of wave function which would appropriately take into account magnetic-field induced anisotropic effects.…”
supporting
confidence: 58%
“…Combined theoretical and experimental studies from Ashkinadze et al [11] for the effect of an in-plane magnetic field on the photoluminescence (PL) spectrum of modulation-doped heterostructures have suggested that there are remarkable spectral modifications of the PL spectra in both modulationdoped QWs and high-quality heterojunctions, due to Binduced modifications in the direct optical transitions in QWs, and effects on the free holes in heterojunctions, respectively. Also, studies [12] on the magnetic-field effects on indirect excitons in coupled GaAs-(Ga,Al)As QWs reveal that the exciton effective mass is enhanced as the growth-direction magnetic field increases and, at high fields, it becomes larger than the sum of the e and h masses, suggesting that a magnetoexciton is an excitation with effective mass determined by the coupling [5] between the exciton center of mass (CM) motion and internal structure rather than by the masses of its constituents.…”
mentioning
confidence: 99%
See 3 more Smart Citations